2004
DOI: 10.1590/s1678-77572004000100010
|View full text |Cite
|
Sign up to set email alerts
|

Apical displacement produced by rotary nickel-titanium instruments and stainless steel files

Abstract: The aim of this study was to evaluate the apical displacement produced by different rotary nickel-titanium instruments, testing the hypothesis that rotary systems with nickel-titanium instruments produce lower mean values of apical displacement than stainless steel hand instruments. A total of 100 maxillary permanent first molars were selected for the study. The mesiobuccal roots were sectioned at the top cervical third and embedded in blocks of self-curing resin. The specimens were randomly divided into 5 gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…This data is important when planning biomechanical preparation as instruments with different tapers and/or kinematics must be used to allow greater surface contact of the instrument. 17,18 According to Buchanan, 19 one must be aware of the anatomical differences of each third of the root canal to optimize the function of each instrument.…”
Section: Discussionmentioning
confidence: 99%
“…This data is important when planning biomechanical preparation as instruments with different tapers and/or kinematics must be used to allow greater surface contact of the instrument. 17,18 According to Buchanan, 19 one must be aware of the anatomical differences of each third of the root canal to optimize the function of each instrument.…”
Section: Discussionmentioning
confidence: 99%
“…Já nos incisivos centrais, apesar de apresentar também acentuada conicidade, a diferença entre a conicidade dos diâmetros maior e menor foi mais discreta (0,09 mm para o diâmetro maior e 0,07 mm para diâmetro menor). Esse dado torna-se importante no momento do planejamento do preparo biomecânico, em que se deve utilizar instrumentos com diferentes conicidades e/ou cinemáticas que permitiria então maior área de superfície tocada pelo instrumento (VANNI et al, 2004;VANNI et al, 2005). Segundo BUCHANAN (1994), para otimizar a função de cada instrumento é preciso ter conhecimento das diferenças anatômicas de cada terço do canal radicular.…”
Section: Ics Ils Csunclassified
“…The flexibility and fracture resistance of NiTi instruments are 2-3 times higher than those of stainless steel files [27], which makes them more efficient and safer [28]. Another study found that [29], nickel-titanium instruments are less prone to apical deviation than stainless steel instruments, which allows the apical segment to be filled more tightly and improves the success rate of root canal treatment. To sum up, nickel-titanium instruments have the advantages that traditional stainless steel instruments are difficult to replace in various aspects.…”
Section: Advantages Of Niti Instrumentsmentioning
confidence: 99%